Case Report: Clinical and molecular features of a radiosensitive autoimmune polyendocrine syndrome type 1 patient with oral carcinoma - Chikhaoui, Asma; Hammami-Ghorbel, Houda; Najjar, Dorra; Zarraa, Semia; Yahiaoui, Safia; Lessel, Davor; Yacoub-Youssef, Houda (Frontiers in Genetics, 2025)
Autoimmune polyendocrine syndrome type-1 (APS1), also known as autoimmune polyendocrinopathy–candidiasis–ectodermal dystrophy (APECED), is an autoimmune genetic disease characterized by multiple endocrine disorders, chronic mucocutaneous candidiasis, and various ectodermal defects. Untreated candidiasis can increase the risk of oral cancer due to recurrent fungal infections. Radiotherapy is a curative option that can trigger an antitumoral response. However, exaggerated radiation-induced cytotoxicity can hinder this curative modality. APECED is caused by loss-of-function mutations in the autoimmune regulator AIRE gene, with only a few cases reported in Tunisia. In this study, we report the clinical, genetic, and molecular characteristics of a patient with APECED syndrome. This patient was initially referred for genetic inquiry due to extreme sensitivity to radiotherapy after developing oral squamous-cell carcinoma. Whole-exome sequencing (WES) was performed to identify disease-causing mutations. A set of candidate genes was further analyzed using real-time quantitative polymerase chain reaction (RT-qPCR) to explore the possible underlying interaction between the detected variant and altered gene expression in inflammatory pathways. We report a loss-of-function, germline, homozygous variant in the AIRE gene associated with APECED syndrome and a gain-of-function variant in mitogen-activated protein kinase kinase kinase 3 (MAP3K3), previously identified in patients with cerebral cavernous malformations (CCMs). Unexplained inflammatory and biochemical manifestations, including increased leukocyte, neutrophil, and C-reactive protein (CRP) levels, were noted. MAPK signaling is organized as a three-tier cascade, in which MAP3Ks activate MAP2Ks, which, in turn, activate MAPKs (ERK, p38, and JNK). These pathways regulate key cellular processes, such as proliferation, differentiation, and stress responses, with each kinase having distinct substrate specificity. Analysis of candidate gene expression interacting with the two key genes indicated the overexpression of p38, TNF-α, and STAT3, which may be associated with these manifestations. Our results underline the impact of WES in clinical diagnosis and confirm the impact of the identified variants on disease manifestation. We also suggest that the co-occurrence of APECED syndrome and a possible variant causing CCMs may be involved in the poor survival of atypical oral carcinoma cases and radiation-induced cytotoxicity.